Shorter Phosphorodiamidate Morpholino Splice-Switching Oligonucleotides May Increase Exon-Skipping Efficacy in DMD - Akpulat, Ugur; Wang, Haicui; Becker, Kerstin; Contreras, Adriana; Partridge, Terence A.; Novak, James S.; Cirak, Sebahattin (Elsevier BV, 2018)
Duchenne muscular dystrophy is a fatal muscle disease, caused by mutations in DMD, leading to loss of dystrophin expression. Phosphorodiamidate morpholino splice-switching oligonucleotides (PMO-SSOs) have been used to elicit the restoration of a partially functional truncated dystrophin by excluding disruptive exons from the DMD messenger. The 30-mer PMO eteplirsen (EXONDYS51) developed for exon 51 skipping is the first dystrophin-restoring, conditionally FDA-approved drug in history. Clinical trials had shown a dose-dependent variable and patchy dystrophin restoration. The main obstacle for efficient dystrophin restoration is the inadequate uptake of PMOs into skeletal muscle fibers at low doses. The excessive cost of longer PMOs has limited the utilization of higher dosing. We designed shorter 25-mer PMOs directed to the same eteplirsen-targeted region of exon 51 and compared their efficacies in vitro and in vivo in the mdx52 murine model. Our results showed that skipped-dystrophin induction was comparable between the 30-mer PMO sequence of eteplirsen and one of the shorter PMOs, while the other 25-mer PMOs showed lower exon-skipping efficacies. Shorter PMOs would make higher doses economically feasible, and high dosing would result in better drug uptake into muscle, induce higher levels of dystrophin restoration in DMD muscle, and, ultimately, increase the clinical efficacy.
Keywords: Therapeutics. Pharmacology; RM1-950; Article; 3. Good health